Boundary effects on vortex flow - Glasser, M.L.; Davies, K.T.R. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
We consider a simple model for a vortex ring in an incompressible, irrotational fluid within an infinite circular cylinder. The effects of the boundary, at which the radial derivative of the flow potential is required to vanish, on the axial flow is examined and found to be negligible as long as the cylinder radius is at least twice that of the vortex ring.